2000
DOI: 10.1093/emboj/19.18.5019
|View full text |Cite
|
Sign up to set email alerts
|

An alternative protein splicing mechanism for inteins lacking an N-terminal nucleophile

Abstract: Variations in the intein-mediated protein splicing mechanism are becoming more apparent as polymorphisms in conserved catalytic residues are identi®ed. The conserved Ser or Cys at the intein N-terminus and the conserved intein penultimate His are absent in the KlbA family of inteins. These inteins were predicted to be inactive, since an N-terminal Ala cannot perform the initial reaction of the standard protein splicing pathway to yield the requisite N-terminal splice junction (thio)ester. Despite the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(168 citation statements)
references
References 45 publications
4
164
0
Order By: Relevance
“…These results were similar to those observed after mutation of the Mja KlbA (Ala1) and MP-Be DnaB (Pro1) intein Ntermini in that some mutations reduced the reactivity of the N-terminal splice junction, while others did not. 5,12,13 However, the relative amounts of products observed with each amino acid were usually specific to the intein, which is also true for all positions tested in this study.…”
Section: Mutagenesis Of Conserved Residues In the Dra Snf2 Inteinmentioning
confidence: 66%
See 2 more Smart Citations
“…These results were similar to those observed after mutation of the Mja KlbA (Ala1) and MP-Be DnaB (Pro1) intein Ntermini in that some mutations reduced the reactivity of the N-terminal splice junction, while others did not. 5,12,13 However, the relative amounts of products observed with each amino acid were usually specific to the intein, which is also true for all positions tested in this study.…”
Section: Mutagenesis Of Conserved Residues In the Dra Snf2 Inteinmentioning
confidence: 66%
“…[1][2][3][4][5] Two variations in the intein-mediated protein splicing mechanism were previously described, which involve direct attack on an amide bond at the N-terminal splice junction to generate a BI. [5][6][7]12,13 In Class 2 inteins, exemplified by the Methanococcus jannaschii (Mja) KlbA intein, 12,13 the Block G BI (III) is formed by nucleophilic attack of Cysþ1 on the peptide bond at the N-terminal splice junction (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in nucleophiles and conserved residues have become more evident as more inteins have been sequenced. A second protein splicing mechanism has been determined for inteins lacking an N-terminal nucleophile [5].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the Methanococcus jannaschii (Mja) KlbA intein showed that (a) it spliced efficiently in Escherichia coli, (b) included the standard branched intermediate, (c) Cys + 1 was required for splicing and thiol-induced N-terminal cleavage of the branched intermediate, (d) the intein C-terminal Asn was required for C-terminal cleavage, (e) the Block B Thr and His activated the N-terminal splice junction, and (f) the standard linear thioester was observed after 'reversion' of Ala1 to Cys (15). These data support a 3-step mechanism in which Cys + 1 directly attacks an amide bond at the N-terminal splice junction resulting in formation of the normal branched intermediate.…”
Section: Ala1 Inteinsmentioning
confidence: 99%